Demographic Characteristics, Clinical Features, and Laboratory-Workup of Pediatric Patients Infected With COVID-19 at Setif, Algeria - Zahir, Salman (International Journal of Pathology, 2022)
Introduction: Since the outbreak of SARS-COV-2 in 2019, many studies have focused on the features of this infection in adults, nonetheless, the demographic, clinical, and laboratory characteristics of children with Covid-19 are not well-documented. Objective: To identify clinical features, and laboratory workup of paediatric sufferers infected with Covid-19. Materials &Methods: This was a retrospective study, which included laboratory-confirmed Covid-19 cases of 30 paediatric patients who consulted the Public Hospital Establishment El Eulma, Setif, Algeria, from April , 2020 to August , 2021. Data were recorded on a questionnaire in which demographic characteristics, clinical features, lab workup and treatment were interrogated, and outcome data were analyzed. Results: 17/30 patients were of 2-15 years of age, 12/30 patients were of 1 month to < 2 years of age, while 1/30 patient was less than one month of age. 43% of cases had a Covid-19 close contact history. The entire paediatric cases showed mild to moderate clinical features. Upon presentation, the most preponderant symptoms were fever (24/30:80%) and cough (18/30:60%). Laboratory data revealed lymphopenia among 27/30 (90%) cases, although the C-reactive protein and D-Dimer levels were raised in most cases. 19/30 had pathological findings on their Chest X-ray radiographs. The treatment modality widely used was antibiotics in most patients (28/30:93%). Conclusion: Covid-19 was contagious in children of all ages. Compared to adult patients, clinical symptoms were typically less severe, even though the outcome of the disease has been moderately favourable with no fatality.